Chromosomally integrated human herpesvirus 6: questions and answers - Pellett, Philip E.; Ablashi, Dharam V.; Ambros, Peter F.; Agut, Henri; Caserta, Mary T.; Descamps, Vincent; Flamand, Louis; Gautheret-Dejean, Agnès; Hall, Caroline B.; Kamble, Rammurti T.; Kuehl, Uwe; Lassner, Dirk; et al. (Reviews in medical virology, 2012)
SUMMARY Chromosomally integrated human herpesvirus 6 (ciHHV‐6) is a condition in which the complete HHV‐6 genome is integrated into the host germ line genome and is vertically transmitted in a Mendelian manner. The condition is found in less than 1% of controls in the USA and UK, but has been found at a somewhat higher prevalence in transplant recipients and other patient populations in several small studies. HHV‐6 levels in whole blood that exceed 5.5 log10 copies/ml are strongly suggestive of ciHHV‐6. Monitoring DNA load in plasma and serum is unreliable, both for identifying and for monitoring subjects with ciHHV‐6 due to cell lysis and release of cellular DNA. High HHV‐6 DNA loads associated with ciHHV‐6 can lead to erroneous diagnosis of active infection. Transplant recipients with ciHHV‐6 may be at increased risk for bacterial infection and graft rejection. ciHHV‐6 can be induced to a state of active viral replication in vitro. It is not known whether ciHHV‐6 individuals are put at clinical risk by the use of drugs that have been associated with HHV‐6 reactivation in vivo or in vitro. Nonetheless, we urge careful observation when use of such drugs is indicated in individuals known to have ciHHV‐6. Little is known about whether individuals with ciHHV‐6 develop immune tolerance for viral proteins. Further research is needed to determine the role of ciHHV‐6 in disease. Copyright © 2011 John Wiley & Sons, Ltd.